Desafios na análise de benzofenonas em leite materno por injeção direta de amostras usando cromatografia líquida hifenada à espectrometria de massa - Costa, Welma Beatriz (2018)
As a solution to the paradigm of achieving maximum efficiency in a shorter analysis time, Ultra High-performance Liquid Chromatography (UHPLC) coupled to mass spectrometry (MS / MS) have been successfully explored. The biggest problem still liesin sample preparation which causes waste of time and generates residue, demanding usually high use of organic solvents. Methods by direct injection of samples furnishes more efficient and greener approaches and have been efficiently used for LC-MS/MS analysis. The present work describes the challenges involved in the quantification of three benzophenones in breast milk by direct injection of the sample using albumin serum bovine restricted access phases (RAM-BSA). This work describes the results obtained for the determination in breast milk of 2,4-dihydroxybenzophenone (BP-1), 2-hydroxy-4-methoxybenzophenone (BP-3) and 2-hydroxy-4-methoxybenzophenone sulfonic acid (BP-4). . The results of obtained showed protein exclusion levels greater than 82% for three different aliquots (n = 3). The studies of matrix effect, process efficiency and recovery were not satisfactory due to strong interaction of analytes with the RAM-BSA phases and also to memory effect. Sample preparation by precipitation of protein was used as a proof of concept but the memory effect remained even when we used different analytical columns, different elution modes, and bovine milk as a matrix, indicating contamination of the chromatographic system and making it impossible for the validation of the method. The screening of breast milks samples by LC-HRMS obtained from 26 different mothers allowed the identification of BP-1, BP-3 and BP-4 in 88% of the analyzed samples.